Revolutionizing Travel : The Impact of Generative AI on Personalization and Efficiency in the Tourism Industry - Chakraborty, Debarun (Indian Journal of Marketing, 2024)
Purpose : This study looked at the social, emotional, and functional values that influence users’ intention to use travel and tourism apps (TTA) and their trust in them, among other factors that affect their usage, in order to investigate the impact of generative artificial intelligence (GAI) content on TTA. It also explained how, even without any desire to use an app themselves, those who are uninvolved or active may nevertheless be impacted by what other people think of it or whatever information they find on it. Methodology : The study was conducted between December 2023 and May 2024, and the questionnaire was shared with more than 5,000 users. Ultimately, we received 440 replies from the various respondents. Findings : These results demonstrated that when people viewed usage information about friend-recommended apps with positive comments, both social influence processes may be activated; however, only normative information may persuade people not to use those apps if their friends had given them bad reviews. Implications : It also examined potential optimizations for AI integration in the tourism industry. Additionally, this work addressed ethical and demographic issues related to this technology; as a result, further research on the broader effects of AI technology on the industry is feasible. Originality : This study has been built on how consumption values affected the intention to use GAI-based TTA in the Indian context.